The rapid change in mental health among college students after introduction of on-campus quarantine during the 2022 Shanghai COVID-19 lockdown - Ma, Dongni; Kuang, Yifang; Lan, Zhaohui; Zeng, Suhua; Li, Yi; Shang, Mengnan; Zhang, Ru-Yuan; Zhao, Binglei; Li, Weidong (Frontiers in Public Health, 2023)
Objectives： Among various impacts of disaster-related emotions, quarantine has been proven to result in significantly increased mental health problems. Studies on psychological resilience in outbreaks of epidemics always focus on long-term social quarantine. However, studies on how rapidly the negative mental health outcomes and how they change over time are insufficient. We evaluated three-time courses of psychological resilience in a university in Shanghai to investigate the influence of an unexpected change in young adults. Methods A structured online questionnaire was applied with retrospective cohort trials. Before March 9th (Period 1), individuals performed activities without restrictions. From 9th to 23rd (Period 2), the majority of students were asked to stay in their dormitories on campus. From 24th March to early April (Period 3), restrictions are relax in that students were gradually allowed to take necessary activities on campus. We quantify dynamic changes in depression severity during three periods. The survey included five classes of self-reported questions: Demographic information, lifestyle/ activity restriction, COVID-19 related background, and the Beck Depression Inventory 2nd edition. Findings: This study involved 274 participants. A remarkable increase in depression was observed in university students after two-week quarantine. The portion of students with depression started at 9.1% before quarantine and rapidly increased to 36.1% right after quarantine. Depressive symptoms reverse imperceptibly over time in Period 3. Depression can be predicted by food supplement satisfaction and the duration of physical fitness per day. Interestingly, the quarantine-related psychological distress was more evident in students who have romantic relationships than singles.